Assessing the ecotourism carrying capacity and other limits of acceptable change for ecotourism development planning and management the case of the Municipality of Plaridel, Quezon province, Philippines - Rossetti, Isabela Braz (School of Urban and Regional Planning, University of the Philippines Diliman, 2024)
The coastal municipality of Plaridel in Quezon Province exhibits strong potential for local ecotourism development as highlighted in various local plans and project proposals. One proposed ecotourism circuit in Barangay Ilosong features several nature-based attractions. However, the absence of dedicated ecotourism and management plans in the municipality leaves these sites in Barangay Ilosong vulnerable to the negative impacts of unregulated and unmonitored visitation. Given these circumstances, the study aims to identify the most appropriate ecotourism management measures for Barangay llosong through ecotourism carrying capacity estimation and the Limits of Acceptable Change (LAC) framework, supplemented by site potential evaluation and local policy analysis.